INTERRELATIONS OF SUSTAINABLE TRANSPORTATION SYSTEMS AND REGIONAL ECONOMIC DEVELOPMENT - Karimboyev, Dilshod (University Research Base, 2024)
This paper explores the intricate interrelations between sustainable transportation systems and regional economic development, with a focus on the evolving policies and strategies in Uzbekistan. By examining both the opportunities and barriers to developing sustainable transport systems, this paper underscores the importance of innovative financing mechanisms, policy reforms, and strategic partnerships to support regional economic growth and environmental sustainability.